Deletion of the rel gene in Mycobacterium smegmatis reduces its stationary phase survival without altering the cell-surface associated properties - Mathew, Renjith; Ojha, Anil Kr; Karande, Anjali A.; Chatterji, Dipankar (Current science (Bangalore), 2004)
Dormant or latent physiology of the mycobacterial species is a subject of current investigation in order to understand the long-term persistence of these organisms inside the host. It is argued that the carbonstarved mycobacteria may serve as a good model for the dormant bacilli. The relA/spoT gene is upregulated during carbon starvation in Mycobacterium tuberculosis and the deletion of the gene resulted in reduction of long-term persistence in M. tuberculosis. Overexpression of the gene in M. smegmatis changes the colony morphology of the bacteria. Here we show that knock-out of the relA/spoT gene compromises stationary-phase survival of M. smegmatis. However, the ΔrelA/spoT bacteria show similar profile of glycopeptidolipids as the wild-type bacteria under carbon starvation. We have seen here that M. smegmatis, a nonpathogenic species, upon carbon starvation exhibits reduced association with murine macrophage cell line RAW 264.7 in comparison to M. smegmatis grown in carbon-enriched medium. But the clearance of the bacteria from macrophages takes place in the same window of time in both conditions.